2000
DOI: 10.1091/mbc.11.10.3425
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal Proteomics: Identification of Nucleotide-sensitive Proteasome-interacting Proteins by Mass Spectrometric Analysis of Affinity-purified Proteasomes

Abstract: Ubiquitin-dependent proteolysis is catalyzed by the 26S proteasome, a dynamic complex of 32 different proteins whose mode of assembly and mechanism of action are poorly understood, in part due to the difficulties encountered in purifying the intact complex. Here we describe a one-step affinity method for purifying intact 26S proteasomes, 19S regulatory caps, and 20S core particles from budding yeast cells. Affinity-purified 26S proteasomes hydrolyze both model peptides and the ubiquitinated Cdk inhibitor Sic1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
459
3
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 518 publications
(486 citation statements)
references
References 45 publications
21
459
3
1
Order By: Relevance
“…In the simplest case, FtsH protease, the particle consists 6 copies of a 71 kDa subunit forming a complex of approximately 425 kDa, and in the most complex case, the proteasome, the particle consists of some 40 different subunits forming a complex of 2 MDa molecular weight [3,4]. The subunits are mostly arranged in six or seven subunit rings that stack on top of each other to…”
Section: Atp-dependent Proteasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the simplest case, FtsH protease, the particle consists 6 copies of a 71 kDa subunit forming a complex of approximately 425 kDa, and in the most complex case, the proteasome, the particle consists of some 40 different subunits forming a complex of 2 MDa molecular weight [3,4]. The subunits are mostly arranged in six or seven subunit rings that stack on top of each other to…”
Section: Atp-dependent Proteasesmentioning
confidence: 99%
“…Cells contain a large number deubiquitinating enzymes (DUBs) [20] and at least two of them, Rpn11 and Ubp6, are located in the 19S regulatory particle and as such components of the proteasome [3,4,[21][22][23]. Rpn11 removes entire ubiquitin chains from the substrate by cleaving the isopeptide bond between the substrate and the first ubiquitin to recycle ubiquitin and to allow substrate's degradation [22,23].…”
Section: Substrate Targeting To Proteasesmentioning
confidence: 99%
“…18, May 2007May 1957 the proteasome can be ubiquitinated (Peng et al, 2003) and the proteasome has been suggested to undergo rapid cycles of assembly/disassembly (Babbitt et al, 2005), we first investigated a possible role for polyubiquitination in the maintenance of fully-assembled 26S proteasome complexes. When the chromosomal locus encoding Pre1, an alpha subunit of the 20S core, is replaced by an allele tagged with a Flag epitope, it is possible to obtain intact, active 26S proteasome complexes by a singlestep affinity purification method (Verma et al, 2000). Proteasomes affinity-purified from uba1-204 cells cultured at either 25 or 37°C were found to contain all 20S and 19S subunits with no detectible change in subunit composition ( Figure 4A).…”
mentioning
confidence: 99%
“…An obvious approach to break through this problem is a large-scale physical analysis of the proteasome-interacting proteins (Verma et al 2000). We are attempting to solve the same problem in a different way.…”
mentioning
confidence: 99%